(untitled) (Indian Journal of Child Health, 2021)
Autoimmune polyglandular syndrome-1 (APS-1)also known as autoimmune polyendocrinopathy candidiasis ectodermal dystrophy is a rare autosomal recessive disorder caused by mutation of AIRE gene on chromosome 21q22.3 with an overall prevalence of <1:100,000. Here, we present a 16-year-old male having clinical history of evolution of symptoms for oral candidiasis, hypoparathyroidism, and adrenal insufficiency (AI). He developed rare endocrine and non-endocrine manifestations such as type-1 diabetes (T1D) and autoimmune hepatitis, respectively. The patient while on hormone replacement therapy along with immunosuppressants developed liver cirrhosis and portal hypertension with esophageal varices and candidiasis. Subsequently, he was admitted for complaints of cough, cold and fever and was confirmed to be affected by SARS-CoV-2 by reverse transcription-polymerase chain reaction method. In his prolonged ICU stay of 26 days, he required oxygen therapy, intravenous glucocorticoids, remdesivir, low molecular weight heparin, and hemodynamic support with inotropes. His medical management with subcutaneous insulin therapy and azathioprine was continued. He was discharged after complete resolution of symptoms and negative tests for SARS-CoV-2 and was advised radiological and clinical follow-up. Reports suggest that risk of severe COVID does not increase in patients with AI or autoimmunity. However, our patient possibly developed severe COVID not only due to AI and autoimmunity but also associated rare manifestations like hyperglycemia due to T1D and cirrhosis. Thus, good glycemic control and well-tolerated modern immunosuppressant therapy may be useful in improving prognosis of severe COVID-19 illness in patients with APS-1.